Adolescent athletes` perceptions of both their coachs` leadership and their personal motivation - López de Subijana, C.; Martin, L. J.; Tejón, O.; Côté, J. (Perceptual and Motor Skills, 2021)
Previous studies, framed within the full range leadership approach, have described how the coach`s interpersonal behaviors affected athletic outcomes. However researchers have yet to explore how specific leadership behaviors (transformational vs transactional), as perceived by athletes, may affect athletes` motivation. The aim of this study was to further examine the link between coaches` leadership behaviors and athletes` motivation among high achieving adolescent athletes. Two-hundred and twenty-three elite youth athletes (M = 15.4 years; SD = 1.6; 53.4% male and 46.6% female) responded to questionnaires pertaining to their coaches` leadership and their individual motivation levels. We found a direct and linear relationship between transformational leadership and intrinsic motivation, and between transactional leadership and external regulation. None of the moderators we studied (age, gender, age group category, and sport skill level) moderated relations between coaches` leadership and personal motivation. This research re-emphasized the important interpersonal role that coaches play in athletes` sport development. We recommend that coaches include more interpersonally focused educational programs that emphasize transformational leadership.